2006
DOI: 10.1128/jvi.80.3.1376-1384.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Virus-Associated RNA Is Processed to Functional Interfering RNAs Involved in Virus Production

Abstract: Posttranscriptional gene silencing allows sequence-specific control of gene expression. Specificity is guaranteed by small antisense RNAs such as microRNAs (miRNAs) or small interfering RNAs (siRNAs). Functional miRNAs derive from longer double-stranded RNA (dsRNA) molecules that are cleaved to pre-miRNAs in the nucleus and are transported by exportin 5 (Exp 5) to the cytoplasm. Adenovirus-infected cells express virus-associated (VA) RNAs, which are dsRNA molecules similar in structure to pre-miRNAs. VA RNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 50 publications
6
162
0
2
Order By: Relevance
“…9 Luciferase was quantified from images obtained using the Living Image 2.20 software (Xenogen). Firefly luciferase activity was quantified in liver extracts by using the Luciferase System (Promega), as described previously, 35 in a Berthold Luminometer (Lumat LB 9507). Protein concentration was assayed by the Bradford method following the recommendations of the supplier.…”
Section: Analysis Of Luciferase Expressionmentioning
confidence: 99%
“…9 Luciferase was quantified from images obtained using the Living Image 2.20 software (Xenogen). Firefly luciferase activity was quantified in liver extracts by using the Luciferase System (Promega), as described previously, 35 in a Berthold Luminometer (Lumat LB 9507). Protein concentration was assayed by the Bradford method following the recommendations of the supplier.…”
Section: Analysis Of Luciferase Expressionmentioning
confidence: 99%
“…VA1 RNAs are 160-nt long and can be recognized by Exp-5 via their minihelix RNA motif (63), which are dsRNA molecules similar in structure to pre-miRNAs (64). Exp-5 directly interacts with VA1 RNA in a Ran·GTP-dependent manner (63).…”
Section: Exportin-5 and Adenovirus Infectionmentioning
confidence: 99%
“…Later, it was found that small RNAs derived from VA1 RNAs, similar to miRNAs, can be found in adenovirus-infected cells (64). These small RNAs are efficiently bound by Ago2, and behave as functional siRNAs, in that they inhibit the expression of reporter genes with complementary sequences.…”
Section: Exportin-5 and Adenovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 In light of this, we carried out additional experiments to address whether EBER RNAs might influence RNAi. Results from our control experiments shown in Figures 3a and b indicated that the partial EBER sequences produced from pEBER1-T6 and pE-BER2-T6 had minimal influence on the expression of luciferase reporter.…”
Section: Induction Of Rnai By Eber-shrna Transcriptsmentioning
confidence: 99%